Long-term observation of estimated fluid volume reduction after the initiation of ipragliflozin in patients with type 2 diabetes mellitus: a sub-analysis from a randomized controlled trial (PROTECT) - Atsushi Tanaka; Takumi Imai; Shigeru Toyoda; Kazuhiro Sugimoto; Ruka Yoshida; Machi Furuta; Koichi Node; the PROTECT Investigators (Diabetology & Metabolic Syndrome, 2023)
Abstract Backgrounds/Aim Recent studies have shown that the addition of sodium-glucose co-transporter 2 (SGLT2) inhibitors gradually reduces the estimated fluid volume parameters in a broad range of patient populations, suggesting that this mediates the clinical benefits of SGLT2 inhibitors in preventing heart failure. Here, we sought to examine the long-term (24 months) effect of the SGLT2 inhibitor ipragliflozin on the estimated fluid volume parameters in patients with type 2 diabetes mellitus (T2DM). Methods In this prespecified sub-analysis of the PROTECT (Prevention of Atherosclerosis by SGLT2 Inhibitor: Multicenter, Randomized Controlled Study) trial, which was an investigator-initiated, multicenter, prospective, randomized, open-label, clinical trial primarily designed to evaluate the effect of ipragliflozin treatment administered for 24 months on carotid atherosclerosis in patients with T2DM, we evaluated serial changes in estimated plasma volume (ePV, %) calculated using the Straus formula and estimated extracellular volume (eEV, mL) calculated by the body surface area by 24 months following the initiation of 50-mg ipragliflozin once daily and compared them with those following standard care for T2DM (non-SGLT2 inhibitor use). Results This sub-analysis included 464 patients (ipragliflozin, n = 232; control, n = 232), a full analysis set of the PROTECT trial. In an analysis using mixed-effects models for repeated measures, relative to the control group, ipragliflozin significantly reduced ePV by − 10.29% (95% confidence interval [CI]  − 12.47% to − 8.11%; P < 0.001) at 12 months and − 10.76% (95% CI − 12.86% to − 8.67%; P < 0.001) at 24 months. Additionally, ipragliflozin significantly reduced eEV by − 190.44 mL (95% CI − 249.09 to − 131.79 mL; P < 0.001) at 12 months and − 176.90 mL (95% CI  − 233.36 to − 120.44 mL; P < 0.001) at 24 months. The effects of ipragliflozin on these parameters over 24 months were mostly consistent across various patient clinical characteristics. Conclusions This prespecified sub-analysis from the PROTECT trial demonstrated that ipragliflozin treatment, compared with the standard care for T2DM, reduced two types of estimated fluid volume parameters in patients with T2DM, and the effect was maintained for 24 months. Our findings suggest that SGLT2 inhibitor treatment regulates clinical parameters incorporated into the calculating formulas analyzed and consequently fluid volume status for the long-term, and this may be at least partly associated with clinical benefits from chronic use of SGLT2 inhibitors. Trial registration Japan Registry of Clinical Trials, ID jRCT1071220089